Pemberdayaan Masyarakat Kelurahan Wonokusumo Melalui Budidaya Tanaman Pakcoy Menggunakan Hidroponik Wick System - Anjarwati, Dian; Permadani, Kezia Aquilla; Aini, Risma Qurrotu; Januar, Muhammad Kiki; Rachmah, Salsabila Auliya; Nadofah, Nadofah (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
The problem of limited land in densely populated areas, particularly in Wonokusumo Village, Semampir District, Surabaya City, is a major obstacle in the community's efforts to meet food needs independently. This condition has prompted the need for innovations that can address the challenge of limited space while increasing food self-sufficiency. One step taken is community empowerment through the cultivation of bok choy using a wick hydroponic system. This activity is designed through several stages: observation and surveys, program planning, coordination with relevant parties, outreach and material delivery, hydroponic cultivation practices (seeding, monitoring, wick system installation), and the final stage of transplanting. The results of the activity indicate that this hydroponic method is relatively easy to understand, does not require a large area of ​​land, and is able to produce plants suitable for consumption. In addition to providing a solution for providing healthy food, this system also has the potential to increase small business opportunities for residents. The enthusiasm shown by residents of RW 14, especially the women in the farming group, is a positive sign of the program's initial success. Going forward, it is hoped that this activity can be continued independently by the community, thereby supporting food self-sufficiency and improving family welfare.